How can we achieve a (truly) widespread implementation of education in relational, emotional and sexual life (EVRAS) in Brussels? - Alice Lannoo; Claire Duchêne; Isabelle Godin; Ilan Tojerow (Brussels Studies)
Education in relational, emotional and sexual life (EVRAS) is a project which has been in place for many years in French-speaking BCR. Despite the active involvement of politicians, numerous stakeholders and schools, it took more than ten years after its integration into the missions of education for EVRAS to become compulsory as of the 2023 school year, in a minimal form. The lack of a true implementation of EVRAS throughout schooling is problematic and contributes to the social inequalities in health which already exist in Brussels. This study is part of the impetus recently given by COCOF and aims to contribute to the definition of future public policies in this area, by proposing three scenarios for the widespread introduction of EVRAS in French-language compulsory education in Brussels, each accompanied by a budget model.